UK transport decoupling: On track for clean growth in transport?. (May 2020) - Nelson, Ewan; Warren, Peter
Highlights: Fills a gap between academic and policy/grey literature on decoupling in transport. A novel policy-orientated decoupling analysis methodology is developed. Identifies a lack of significant decoupling in UK transport between 1997 and 2015. Decoupling within planetary boundaries requires a large shift from current trends. Improvements in decoupling analysis for transport policy research are suggested.